1998
DOI: 10.1103/physrevlett.80.4277
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance of Atomic Junctions

Abstract: We report the behavior of the electrochemical capacitance for a variety of atomic junctions using ab initio methods. The capacitance can be classified according to the nature of conductance and shows a remarkable crossover from a quantum dominated regime to that of a classical-like geometric behavior. Clear anomalies arise due to a finite density of states of the atomic junction as well as the role played by the atomic valence orbitals. The results suggest several experiments to study contributions due to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 13 publications
5
61
0
Order By: Relevance
“…In addition to the geometry and dielectric constant, which are sufficient to determine the capacitance at the macroscales and microscales, the capacitance of a nanostructure can be affected by quantum effects [1]. Theoretical studies have shown the capacitance quantum corrections to come mainly from the finite density of states (DOS) of the nanosized electrodes, the finite screening length to the electron-electron interaction, and quantum tunneling [1][2][3][4][5][6]. So far, no experiment has been made to demonstrate these quantum effects, in spite of its importance in many phenomena such as Coulomb blockade (CB) and device applications.…”
mentioning
confidence: 99%
“…In addition to the geometry and dielectric constant, which are sufficient to determine the capacitance at the macroscales and microscales, the capacitance of a nanostructure can be affected by quantum effects [1]. Theoretical studies have shown the capacitance quantum corrections to come mainly from the finite density of states (DOS) of the nanosized electrodes, the finite screening length to the electron-electron interaction, and quantum tunneling [1][2][3][4][5][6]. So far, no experiment has been made to demonstrate these quantum effects, in spite of its importance in many phenomena such as Coulomb blockade (CB) and device applications.…”
mentioning
confidence: 99%
“…The first-principles moleculardynamics simulations based on solving the self-consistent electron structures remedy this deficiency. 8,21 Indeed, this kind of simulation 8,22 shows that the atomic geometries at the neck can be derived from those of isolated small atomic clusters, the stability of which derives from the closed-shell structures of valence electrons. The role of the valenceelectron structure is emphasized in jellium-type models, [10][11][12][13] which completely ignore the detailed ionic structure.…”
Section: Introductionmentioning
confidence: 96%
“…(18,19,20,21,17) form the basis for numerical calculations of TMR I-V curves beyond what has been done before, since it is a gauge invariant formula. In a typical numerical analysis, one computes Green's functions G r and the coupling matrix Γ using tight-binding models 22 ; and the Poisson equation can be solved using very powerful numerical techniques 25 . Numerical analysis of these expressions is beyond the scope of this paper and in the next section we attempt to obtain the I-V characteristics via analytic means.…”
Section: General Theoretical Formulationmentioning
confidence: 99%